The uses of affect in education: Chilean government policies. Issue 2 (4th March 2017) - Matus, Claudia
ABSTRACT: This article draws attention to the uses of affect to produce specific subjectivities and moralities in educational policies. It highlights the connections between specific ideas of the educated subject, the family role presented in governmental educational policies in Chile, and the ways these ideas are linked to the subjectivities and communities which the market requires to function. My argument is that with different intensities, affect regulation has become a strategic component of a government that articulates the relation between 'right ways to behave at home' and 'school success'. As a result, affect makes conservative cultural dispositions look natural. I use discourse analysis to show how these policies use affect to control and monitor behaviors and personal relations, as well circulating cultural logics and ideological structures. I analyze one particular document to show how affect does not work through meanings per se; rather, it circulates productive ideas of families, students' behaviors, and social and cultural frames to organize a 'good life'.